Methods of detection of crimes in the tax and banking sectors of the Russian economy - Nikishkin A. V., Stepanov I. V. (Economic science today: theory and practice, 2018)
This article discusses various methods of detection and disclosure of economic crimes in the tax and banking sectors of the Russian Federation.
Keywords: коррупция; экономическое развитие; банки; corruption; экономические преступления; banks; economic development; economic crimes; преступное посягательство; interests of society and the state; criminal encroachment; интересы общества; интересы государства